ANALYSIS OF COMPLIANCE FACTORS FOR INDIVIDUAL TAXPAYERS OF BUSINESS ACTORS AT KPP PRATAMA SALATIGA - Devira Nourma Anjani; MI Mitha Dwi Restuti (Berkala Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this study is to analyze the factors that influence individual taxpayer compliance with the enactment of PP. 46 of 2013. In addition, this study also aims to analyze the interaction between attitudes, subjective norms, and perceived behavioral control. The number of samples used is 103 individual taxpayers of certain business actors registered at the KPP Pratama of Salatiga City. The sampling technique was purposive sampling and then processed using SPSS AMOS 22.0. The results of this study indicate that (1) there is no interaction or relationship between attitudes, subjective norms and perceived behavioral control; (2) attitude has a significant positive effect on the intention to behave obediently; (3) subjective norms have no significant effect on the intention to behave obediently; (4) perceived behavioral control has a significant positive effect on the intention to behave obediently; (5) perceived behavioral control has a direct effect on tax compliance; and (6) the intention to behave obediently affects tax compliance.